2008
DOI: 10.2337/dc08-0864
|View full text |Cite
|
Sign up to set email alerts
|

A1C Variability and the Risk of Microvascular Complications in Type 1 Diabetes

Abstract: OBJECTIVE -Debate remains as to whether short-or long-term glycemic instability confers a risk of microvascular complications in addition to that predicted by mean glycemia alone. In this study, we analyzed data from the Diabetes Control and Complications Trial (DCCT) to assess the effect of A1C variability on the risk of retinopathy and nephropathy in patients with type 1 diabetes.RESEARCH DESIGN AND METHODS -A1C was collected quarterly during the DCCT in 1,441 individuals. The mean A1C and the SD of A1C vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
363
5
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(403 citation statements)
references
References 26 publications
23
363
5
12
Order By: Relevance
“…intensive treatment group over time in patients with similar average HbA 1c values in the two groups (5), suggesting that additional factors other than mean HbA 1c may be responsible for this increased retinopathy risk (5)(6)(7). Glycemic variability is now emerging as a possible additional measure of glycemic control, which may be a better predictor of complications than average glycemic measures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…intensive treatment group over time in patients with similar average HbA 1c values in the two groups (5), suggesting that additional factors other than mean HbA 1c may be responsible for this increased retinopathy risk (5)(6)(7). Glycemic variability is now emerging as a possible additional measure of glycemic control, which may be a better predictor of complications than average glycemic measures.…”
mentioning
confidence: 99%
“…A recent meta-analysis concluded that HbA 1c variability, assessed by the SD, is associated with renal disease in type 1 and type 2 diabetes (9). However, no systematic reviews or meta-analyses have evaluated the relationship between long-term glycemic variability and other complications in diabetes, despite contradictory literature providing evidence in support (6,(10)(11)(12)(13)(14)(15) and against (16)(17)(18)(19)(20) such a relationship.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is derived essentially from retrospective epidemiological analyses with hard (microvascular) endpoints [2] and from observational and interventional studies with surrogate endpoints (oxidative stress and endothelial function, assessed with flow-mediated dilation) [3,4]. Clearly, the correlation found between glycaemic variability and microvascular complications/oxidative stress does not necessarily indicate a cause-effect relationship; furthermore, the effect of glycaemic instability on macrovascular disease is not known.…”
mentioning
confidence: 99%
“…Diabetic nephropathy advances through a number of recognisable steps from subclinical disease to the first measurable stage of microalbuminuria (MIC), defined as persistent urinary albumin excretion rates (UAER) of 30-300 mg/24 h, to macroalbuminuria/diabetic nephropathy (DMN) with UAER > 300 mg/24 h. DMN is characterised by declining renal function and ultimately end-stage renal disease. Although positive effects on the development and progression of diabetic nephropathy through strict control of blood glucose [4], blood pressure [5] and, in particular, blockade of the renin-angiotensin system (6, 7) have been reported, it still has not been enough to prevent the high incidence of end-stage kidney damage caused by diabetes. The urinary albumin excretion rate is used to identify patients at risk, but only a fraction of all patients with microalbuminuria progress to DMN.…”
Section: Introductionmentioning
confidence: 99%